VIVÊNCIAS DE FAMILIARES DE PESSOAS COM DEFICIÊNCIA FRENTE AO ISOLAMENTO/AFASTAMENTO SOCIAL DURANTE A PANDEMIA DE COVID-19 - CRISSI, FERNANDA (2022)
Three months after the first diagnosed case, the WHO declared a new virus, SARS- CoV-2, a global pandemic situation. In order to control the spread of the virus, the guidelines were based on measures such as isolation and social distancing, use of a mask and use of alcohol 70%. Isolation measures were imposed on the whole society, but each part of this whole feels its impacts differently. From this point of view, this research aimed to understand how families of people with disabilities experienced the period of isolation/social distancing during the Covid-19 pandemic. The research assumes a qualitative nature and, for its effectiveness, 10 interviews were carried out with family members of people with disabilities at the APAE in the municipality of Guarapuava - PR. Data were analyzed through thematic content analysis, through which 4 categories of analysis were outlined: On support networks and the reality of disability; on the existing Isolation before the Pandemic Isolation; On the Negationist Discourse and the discourses of care for life; and On Normalizing Life with Covid-19. It is necessary to look into this issue so that there is the possibility of planning and implementing policies that guarantee the life of this population at this time.